Employing Molecular Dynamics Simulations to Explore the Behavior of Diphenylalanine Dipeptides in Graphene-Based Nanocomposite Systems - Elena Markopoulou; Panagiotis Nikolakis; Gregory Savvakis; Anastassia N. Rissanou (Inorganics)
Utilizing all-atom molecular dynamics simulations, in the current study, we examine how three different graphene-based nanosheets (pristine graphene, graphene oxide and edge-functionalized graphene) impact the self-assembly mechanism of diphenylalanine dipeptides in aqueous solutions. By comparing the conformational properties and dynamics of diphenylalanine dipeptides in the presence of each nanosheet, we elucidate the effects of the existence of functional groups, their type, and their position on the formed nanostructures. We quantify the interaction energy between diphenylalanine dipeptides and the nanosheets, analyzing various energetic components, to gain insights into the driving forces for the assembly procedure in the nanocomposite systems. Dipeptides readily coat nanosheets due to their high surface affinity. Subsequent diphenylalanine self-assembly is determined by the nanofiller type: in the systems with graphene oxide and edge functionalized graphene, there is an increase of the interfacial layer thickness, while in the system with pristine graphene a structure extended on top of the coating layer is formed. Additionally, we monitor how dipeptides facilitate the dispersion of graphene-based nanosheets in aqueous solution. The findings of this work enhance our understanding of the interplay between diphenylalanine dipeptides and graphene-based nanosheets, paving the way for the rational design of novel materials with tailored properties for specific applications.